Optimalisasi Pedoman Evaluasi Peraturan Perundang-Undangan dalam Mengatasi Hiper-Regulasi di Indonesia - Sujatmiko Sujatmiko; Willy Wibowo; Muhaimin Muhaimin; Yuliyanto Yuliyanto; Eko Noer Kristiyanto; Ulya Fajri Amriyeny; Dian Nurcahya Nurcahya (Badan Strategi Kebijakan Hukum, 2024)
Based on data from the Directorate General of Legislation, as of 2024, Indonesia has a total of 52,676 regulations, which include 1,752 Laws, 217 Government Regulations in Lieu of Laws, 4,899 Government Regulations, 2,380 Presidential Regulations, 18,371 Ministerial Regulations, 5,930 Regulations from Heads of Agencies, and 19,077 Regional Regulations. This extensive regulatory framework indicates a trend of hyper-regulation, overlap, ineffectiveness, and ambiguity. The Ministry of National Development Planning/Bappenas encourages ministries, agencies, and local governments to conduct self-assessments through regulatory analysis and evaluation activities. Following this policy, the National Legal Development Agency/BPHN has been designated as the authority to formulate technical policies for monitoring and reviewing Laws, as well as for the analysis and evaluation of legislation as part of national legal development.This study employs a qualitative approach using Merille S. Grindle's policy implementation model. The findings indicate that the implementation of the guidelines for evaluating legislation (Decision of the Head of the National Legal Development Agency No. PHN-HN.01.03-07 of 2019) has been ineffective. Ministries, agencies, and local governments have not utilized these evaluation guidelines in their regulatory analysis and evaluation activities as outlined in the aforementioned decision. Therefore, a policy recommendation for the National Legal Development Agency is to elevate the legal status of the guidelines for regulatory analysis and evaluation from a Head of Agency Decision to a Regulation of the Minister of Law and Human Rights.